A computationally efficient technique to model depth, orientation and alignment via ray tracing in acoustic power transfer systems. (9th November 2017) - Christensen, David B; Basaeri, Hamid; Roundy, Shad
Abstract: In acoustic power transfer systems, a receiver is displaced from a transmitter by an axial depth, a lateral offset (alignment), and a rotation angle (orientation). In systems where the receiver's position is not fixed, such as a receiver implanted in biological tissue, slight variations in depth, orientation, or alignment can cause significant variations in the received voltage and power. To address this concern, this paper presents a computationally efficient technique to model the effects of depth, orientation, and alignment via ray tracing (DOART) on received voltage and power in acoustic power transfer systems. DOART combines transducer circuit equivalent models, a modified version of Huygens principle, and ray tracing to simulate pressure wave propagation and reflection between a transmitter and a receiver in a homogeneous medium. A reflected grid method is introduced to calculate propagation distances, reflection coefficients, and initial vectors between a point on the transmitter and a point on the receiver for an arbitrary number of reflections. DOART convergence and simulation time per data point is discussed as a function of the number of reflections and elements chosen. Finally, experimental data is compared to DOART simulation data in terms of magnitude and shape of the received voltage signal.